SELECTION OF GOODS DELIVERY SERVICES BASED ON CUSTOMER RELATIONSHIP MANAGEMENT AND SAW METHOD - Wahyudien, Mohammad Arief Nur; Ahistasari, Asih; Kayatun, Siti Nur; Gani, Mardhiah; Wattihelu, Syaiful Akbar (JEMIS (Journal of Engineering & Management in Industrial System), 2024)
Goods delivery services are a principal element in supporting online buying and selling sites. Every year, user figures Internet in Indonesia the more increase value. Matter This in line with change paradigm society which prefer to shop online, where this can save time and the price of goods Which competitive between seller Which One with Which other. Public can choose type service Which will become considering options, choosing a goods delivery service is very important and must be in accordance with the criteria and category of the desired delivery service. The purpose of this research is to select delivery services based on Customer Relationship Management with approach 5 W+1H And know application Simple Additives Weighting (SAW) for selecting the best delivery service as a solution to make it easier for online shop users to choose a delivery service. Based on data collection, the result was that the best delivery service was JNE with a total of 46 respondents using the delivery service and the largest result was 1. After that, service delivery J&T Where amount user service delivery as much 44 respondents with results end of 0.94490. So, based on data analysis using the Simple Additive Weighting method, the best delivery service according to the criteria is JNE.